The application of autochthonous lactic acid bacteria in white brined cheese production - Zorica Radulović; Jelena Miočinović; Predrag Pudja; Miroljub Barać; Zorana Miloradović; Dušanka Paunović; Dragojlo Obradović (Mljekarstvo)
The effects of autochthonous strains of lactic acid bacteria on the characteristics of white brined cheeses were studied throughout 90 days of ripening. Cheese A was produced with strains: Lactococcus lactis ssp. lactis 653, Lactococcus lactis ssp. cremoris 656, Lactococcus lactis ssp. lactis biovar. diacetylactis 07 and Lactobacillus paracasei ssp. paracasei 08 (8:5:5:2) and cheese B with strains: Lactococcus lactis ssp. lactis 195, Lactococcus lactis ssp. cremoris 656 and Lactococcus lactis ssp. lactis biovar. diacetylactis 07 (10:5:5). The lactococci counts in both cheeses and lactobacilli count in cheese A remained at a high level, while lactobacilli count in cheese B increased through the ripening. No significant differences (P<0.05) were found in the gross composition of the experimental cheeses, although the pH values were lower in cheese A. Proteolysis was assessed by the water-soluble nitrogen fractions, 5 %-phosphotungstic-acid-soluble nitrogen fractions and SDSPAGE- electrophoresis. Both experimental cheeses were characterized by a high rate of proteolysis. According to sensory evaluation, experimental cheeses received high total scores. The results show that autochthonous strains of lactic acid bacteria can be successfully applied in white brined cheeses production.